Outcomes After Repair of Pulmonary Atresia With Ventricular Septal Defect and Major Aortopulmonary Collateral Arteries: A Tailored Approach in a Developing Setting - Zou, Ming-Hui; Ma, Li; Cui, Yan-Qing; Wang, Huai-Zhen; Li, Wen-Lei; Li, Jia; Chen, Xin-Xin (Frontiers in Cardiovascular Medicine, 2021)
OBJECTIVES: Pulmonary atresia with ventricular septal defect and major aortopulmonary collateral arteries (PA/VSD/MAPCAs) is complex and diverse that has led to a variety of treatment strategies. Experience has been largely obtained in the advanced countries. The clinical diversity is greater in China. We evaluated our surgical approaches and outcomes of these patients. METHODS: We reviewed 127 patients undergoing varied surgeries in our center in 2010–2019. RESULTS: Thirty patients underwent single-stage complete repair by unifocalizing MAPCAs and VSD closure (aged 3.9–131.4 months, median 22) with 3 (10%) early deaths. Ninety-seven underwent the first-stage rehabilitation strategy including systemic-to-pulmonary shunt in 29 (aged 0.5–144 month, median 8) and palliative RV-PA conduit in 68 (aged 2.2–209.6 months, median 14) with 5 (5.2%) early deaths. Eight-one patients (63.8%) eventually achieved complete repair with a median right/left ventricular (RV/LV) pressure ratio of 0.7 (ranged 0.4–1.0). Fourteen patients (11.0%) accepted palliation as final destination. Survival for the entire cohort was 89.5%, 85.2%, and 76.1% at 1, 5 and 10 years, respectively. Survival for those undergoing complete repair was 88.2% and 76.6% at 1 and 5 year, respectively. RV/LV pressure ratio ≥ 0.8 was risk factor for mortality (HR10.3, p=0.003). CONCLUSIONS: Our cohort, the largest from China, had distinctive clinical features with substantially wider age range and higher RV/LV pressure ratio. Using the combined approaches tailored to individual patients, complete repair was achieved in 64% of patients. The early and intermediate outcomes are acceptable when compared to many of the previous reports.